Pengaruh dan Peran Manajer SDM terhadap Keharmonisan Hubungan Industrial di Kota Batam - Adi Neka Fatyandri; Evi Silvana Muchsinati (Universitas Kristen Maranatha, 2014)
Abstract: The objective of research on industrial relation is to provide a reference to Human Resource (HR) Manager to create a harmonious relationship between management and employees within organization and to describe a strategic role of HR Manager in managing employee’s activities and formulating strategic recommendation to top management. Harmonious relationship can compose a healthy, safety, and productive working environment for stakeholders. In managinghuman resource, an HR Manager is expected to acquiry competences which are related to Human Resource Management, especially competencies on attitude, skilland knowledge in getting the right man on the right place. Long term objective is to enhance the role of HR Manager by actively involved in the industrial relation for maintaining a good relationship and alleviating/ eliminating the industrial relationdisputes. In order to achieve this objective, the role of HR Manager is not only to recruit and to allocate employees but also to build and to maintain a positive communication to the entire employees through formal and informal ones inorganization. In regard with communication, the role of HR Manager may be act as facilitator or mediator, depending on situation occurred. Therefore currently an HR Manager is not only required to master Labor Law but other core competenciessuch communication and negotiation skill. Researcher also recommend the competencies of HR Manager need to be certified in industrial.Keywords: Industrial Relation, Competencies, Human Resource Manager